Prenatal ethanol exposure increased the susceptibility of adult offspring rats to glomerulosclerosis. (15th March 2020) - Chen, Haiyun; Zhu, Yanan; Zhao, Xiaoqi; He, Hangyuan; Luo, Jinsong; Ao, Ying; Wang, Hui
Highlights: PEE increases the susceptibility of offspring to glomerulosclerosis under the high-fat diet feeding after weaning. PEE caused podocytes EMT in offspring. Low expression programming of AT2R mediated susceptibility of male offspring to glomerulosclerosis. GC-IGF1 axis programming mediated susceptibility of female offspring to glomerulosclerosis. Abstract: This study was aimed to investigate the effect of prenatal ethanol exposure (PEE) on the susceptibility of offspring rats to glomerulosclerosis and to explore the mechanism. Pregnant Wistar rats were intragastrically administered ethanol (4g/kg·d) from gestational day (GD) 9 to GD 20, and the control group was given equal volume of normal saline. The offspring rats were all fed with high-fat diet after weaning, and were sacrificed at postnatal week 24 (PW24). The results revealed that the adult offspring kidneys in the male and female PEE groups exhibited higher glomerulosclerosis index and interstitial fibrosis index compared with the high-fat diet control groups, accompanied by elevated serum creatinine level. The protein expression of Nephrin and WT1, which were the marker genes of podocytes, was significantly decreased, whereas the protein expression of desmin and α-SMA, the marker genes of mesenchymal cells, was remarked enhanced in the male and female PEE groups. Compared with the high-fat diet control groups, the mRNA and protein expressions of renal angiotensin II receptor type 2 (AT2R) were decreased in the male PEE group, but increased in the female PEE group. PEE increased the mRNA and protein expressions of glucocorticoid (GC) activation system and inhibited the expression of insulin-like growth factor 1 (IGF1) signaling pathway in male offspring kidney; on the contrary, in female offspring kidney, PEE inhibited the mRNA and protein expression of glucocorticoid activation system and increased the expression of IGF1 signaling pathway. Taken together, PEE increased the susceptibility of the adult offspring to glomerulosclerosis, and the programming of renal AT2R or GC-IGF1 is respectively involved in the toxicity of PEE to the male or female offspring.